Desenvolvimento de planilha eletrônica genérica para orçamento de obras residênciais de pequeno porte - Duarte, Lucas Santos (2012)
To study the economic feasibility of a project, conducting a budget consistent with the fundamental reality is, a poorly prepared budget can compromise the overall planning of a work. A budget must be for more is always an approximation, so the more reliable are the data that comprise this budget, for example, labor, material type, price and so on.Thegreater the chances of a budget reliable. One way to obtain reliable data is through information of works already executed, especially when the labor and construction pattern repeats. For the study of future projects was a survey of the material costs of a small residential project of 70 m² built in the city of Cajati, state of São Paulo. The survey data was obtained using information from the invoices filed the work in question and information of the contractor responsible for carrying out the work. There will be a budget work, only for materials already performed for these data as a basis for future budgets. With the budget of the completed work already accomplished was possible to develop a spreadsheet that allows budgeting works similar pattern with the work budgeted.